UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK MELALUI PEMBELAJARAN INTERAKTIF BERBASIS WORDWALL PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V SDN 40 MATARAM - Eva Sulastri; Baik Nilawati Astini; Mardiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine efforts to improve student motivation and learning outcomes through interactive learning based on wordwalls in Pancasila education learning in class. The type of research used is classroom action research which takes place in two stages, namely pre-learning cycle and learning cycle consisting of four steps, namely planning, action, observation and reflection. This research was conducted at SDN 40 Mataram, with 13 students as research subjects. Based on the research that has been conducted, it was obtained that student learning motivation in the pre-cycle stage was 68.2%, in the first cycle stage it increased to 75.3% after using wordwalls in the learning process. A significant increase occurred after the second cycle stage of 90.2%. As the value of student motivation increases at each stage, student learning outcomes are also directly proportional to that motivation. At the pre-cycle stage, the average value of student learning outcomes was 73 with classical completeness of 53.8%, at the cycle I stage, the average value of student learning outcomes was 77.6 with classical completeness of 84.6%, at the cycle II stage, the average value of student learning outcomes was 88 with classical completeness of 92.3%.